Dielektrické vlastnosti epoxidových pryskyřic - Matoušová, Klára (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2019)
Tato diplomová práce se zabývá základními vlastnostmi epoxidových směsí, jelikož určení základních parametrů připravené epoxidové směsi by v případě příznivých výsledků mohlo vést ke snížení počtu vad v epoxidem zalévaných přístrojových transformátorech. Jelikož působení vlivů v průběhu výroby transformátorů, způsobující nekvalitu, je velmi rozsáhlé, je největší důraz kladen právě na vliv složení epoxidové licí směsi. V práci je popsána technologie výroby včetně používaných metod a materiálů. Dále složení epoxidových pryskyřic a mechanismy při jejich vytvrzování. Rovněž jsou zahrnuty definice základních vlastností dielektrických materiálů a popis diagnostických metod sloužících k určování permitivity, ztrátového činitele a vnitřní rezistivity. V rámci experimentální části byly stanoveny a vysušeny vhodné odlitky získaných vzorků a následně byla provedena měření základních elektrických vlastností v teplotních a kmitočtových závislostech. Dále následuje srovnání jednotlivých sad vzorků a zhodno-cení jejích elektrických vlastností.

This diploma thesis deals with the fundamental properties of epoxide mixtures, as determining of these fundamental properties of epoxide mixtures could in the case of favorable results lead to diminishing the amount of defects in epoxide-embedded instrument transformers. As the influence of effects in the manufacturing process of transformers causing poor quality is very extensit, the biggest emphasis is laid capitally on the influence of the epoxide casting mixture composition. The thesis describes the manufacture technology including used methodics and materials. The compositions of epoxide resins and the mechanisms of their curing. Also, the definitions of fundamental properties of dielectric materials and the description of diagnostic methods used to relative permitivity, dissipation factor and inner resistivity are included. suitable casts of acquired samples were set and dried out within the experimental part, followed by measurement of fundamental electrical properties in temperature and frequency relations. Hereafter a comparison of individual samples and the evaluation of their electrical properties will be carried out.
Dielectric properties of epoxy resins
Keywords: Přístrojové transformátory; dielektrika; reaktoplasty; elektroizolační hmoty; epoxidové pryskyřice; elektrické vlastnosti; rezistivita; permitivita; ztrátový činitel; SYNPO a.s.; ABB s.r.o.; Instrument transformer; dielectric materials; thermosets; electrical insulation materials; epoxy resins; electrical properties; rezistivity; permitivity; dissipation factor; SYNPO a.s.; ABB s.r.o.